The consensus on the prevention and correction of hyperglycemia in patients with HR+ HER2- metastatic breast cancer treated with alpelisib - Natalya V. Mazurina (IP Habib O.N., 2021)
The consensus on the prevention and correction of hyperglycemia in patients with HR+ HER2- metastatic breast cancer treated with alpelisib was developed by the experts of the Russian Association of Endocrinologists and the Russian Society of Clinical Oncology. The consensus contains recommendation on risk assessment, prophylaxis and correction of hyperglycemia regarding the baseline metabolic status of the patients.